Ring opening polymerisation of ɛ-caprolactone with novel microwave magnetic heating and cyto-compatible catalyst - Wang, Kaiyang; Ni, Ming; Dundas, Adam A.; Dimitrakis, Georgios; Irvine, Derek J. (Frontiers in Bioengineering and Biotechnology, 2023)
We report on the ring-opening polymerization of ɛ-caprolactone incorporated with a magnetic susceptible catalyst, FeCl3, via the use of microwave magnetic heating (HH) which primarily heats the bulk with a magnetic field (H-field) from an electromagnetic field (EMF). Such a process was compared to more commonly used heating methods, such as conventional heating (CH), i.e., oil bath, and microwave electric heating (EH), which is also referred to as microwave heating that primarily heats the bulk with an electric field (E-field). We identified that the catalyst is susceptible to both the E-field and H-field heating, and promoted the heating of the bulk. Which, we noticed such promotion was a lot more significant in the HH heating experiment. Further investigating the impact of such observed effects in the ROP of ɛ-caprolactone, we found that the HH experiments showed a more significant improvement in both the product Mwt and yield as the input power increased. However, when the catalyst concentration was reduced from 400:1 to 1600:1 (Monomer:Catalyst ratio), the observed differentiation in the Mwt and yield between the EH and the HH heating methods diminished, which we hypothesized to be due to the limited species available that were susceptible to microwave magnetic heating. But comparable product results between the HH and EH heating methods suggest that the HH heating method along with a magnetic susceptible catalyst could be an alternative solution to overcome the penetration depth problem associated with the EH heating methods. The cytotoxicity of the produced polymer was investigated to identify its potential application as biomaterials.